Responses of soil microbial community structure to stand densities of Chinese fir plantations. Issue 3 (4th May 2019) - Wang, Chaoqun; Xue, Lin; Dong, Yuhong; Hou, Lingyu; Wei, Yihui; Jiao, Ruzhen
ABSTRACT: Plant-microorganism interactions have an important effect on plant growth and yield. However, how stand densities of Chinese fir plantations to drive change in the microbial structure remains unclear. This study used gas chromatography (GC) to determine the biomass of Phospholipid Fatty Acids (PLFA) of soil microorganisms in the topsoil (0–20 cm) of Chinese fir plantations of five initial densities (D1: 1667 stems/hm 2, D2: 3333 stems/hm 2, D3: 5000 stems/hm 2, D4: 6667 stems/hm 2, and D5: 10, 000 stems/hm 2 ); stand densities at sampling were D1: 1578 stems/hm 2, D2: 2294 stems/hm 2, D3: 2617 stems/hm 2, D4: 2789 stems/hm 2, and D5: 2461 stems/hm 2 . We found that the microbial biomass was significantly affected by both the initial density and the subsequent density of Chinese fir plantation. Overall, the low-density plantation was more conducive to increasing the microbial structure diversity. The ratio of fungal biomass to bacterial biomass was higher at the low density (D1 and D2) compared to the high density (D3, D4, and D5), while the ratio of the biomass of Gram-positive bacteria to the biomass of Gram-negative bacteria was opposite, which suggest that high-density Chinese fir plantations are exposed to greater environmental stresses than low-density Chinese fir plantations. We showed that the biomass of PLFA is significantly affected by soil capillary porosity, maximum water-holding capacity, pH, alkali available N, and available P. Together, we provide a theoretical basis for the management of Chinese fir plantations and a broader perspective for better understanding and estimating the influences of stand densities on plantations in the regional and world scales.